Pendampingan Revitalisasi Kegiatan Keagamaan masa Pandemi COVID-19 bagi Remaja Masjid (REMAS) Subulussalam Dusun Sidodadi Desa Canggu Kecamatan Badas Kabupaten Kediri - Ahmad Chamdani Labib; Miftahul Arif (LP3M IAIFA Kediri, 2020)
Religious activities located in the mosque environment that can fortify the jama'ah from negative influences, especially for the cadres of the successor to the religious struggle, namely the youth of the mosque (REMAS) must always be maintained its exhibition. Based on this context in lasanakalnlah activities to assist in revitalizing religious activities for REMAS. This revitalization activity is specifically for the teenagers of subulussalam mosque in Sidodadi hamlet of Canggu village of Badas district of Kediri district. It is felt very necessary to do to maximize religious activities in mosques and also to stem negative influences such as online games that are able to affect teenagers so as to forget about time and make them neglect the obligation to seek or deepen religious knowledge. In addition, because it is in their hands that will develop or not shi'ar religion in the future. In this activity also involved cooperation with related steakholders such as religious leaders, ta'mir mosque nu branch board, and senior squeeze.